Design of Temperature and Humidity Control of Oyster Mushroom in Kumbung - Winarno Fadjar Bastari; Budi Prijo Sembodo; Teddy Septian Wahyudi (Tibuana, 2022)
Abstrack - Optimal temperature and humidity greatly affect the growth of oyster mushrooms. Cultivation of oyster mushrooms in kumbung is an attempt to control the optimal temperature and humidity for fungal growth. Periodic manual watering was felt to be less effective in controlling temperature and humidity in mushroom kumbung. Current technological developments provide the potential to create automatic control systems to control temperature and humidity in mushroom kumbung. Therefore, in this research, a controller is designed to control temperature and humidity in kumbung mushroom automatically based on a microcontroller. This shows that the control system designed is able to control the temperature and humidity in the mushroom kumbung automatically